Synoptic and Mesoscale Forcing of Southern California Extreme Precipitation. Issue 24 (28th December 2018) - Cannon, Forest; Hecht, Chad W.; Cordeira, Jason M.; Ralph, F. Martin
Abstract: Southern California water resources are heavily dependent on a small number of extreme precipitation events each winter season, which dictate the region's highly variable interannual accumulations. In the Santa Ana River Watershed, on average, three extreme events per year contribute half of annual precipitation, yet there are relatively few studies of the synoptic to mesoscale processes that drive precipitation during these events. This study uses an ingredient‐based approach in identifying the contributions of orographic forcing, dynamical forcing, and convective instability to extreme precipitation in the watershed in 107 storms that produced roughly 50% of all precipitation from 1981 to 2017. The influence of dynamical forcing and convective instability on event precipitation distributions is investigated relative to the dominant influence of orographic forcing that is typically found in landfalling atmospheric rivers. Case studies of two high‐impact events from the 2017 winter season demonstrate differences in the roles of synoptic ascent and mesoscale convective features in modifying precipitation location, rate, and accumulation over the watershed. The 17 and 18 February 2017 case study included a narrow cold‐frontal rainband that produced high‐intensity short‐duration precipitation over low elevations of the watershed. In the 107 extreme event records, similar modification of the precipitation distribution toward non‐orographic rainfall was related to significant changes in the synoptic‐scale circulation that favored enhanced dynamics and upstream ascent associated with frontogenesis. Variability in precipitation mechanisms is of primary interest to weather forecasters and water managers as it modifies event impacts and predictability. Key Points: In the Santa Ana river watershed, 107 extreme events contributed nearly half of total precipitation between 1981 and 2017 Total integrated vapor transport, including in atmospheric rivers, is the leading source of variability in extreme event precipitation The characteristic orogaraphic precipitation distribution in extreme events is modified by synoptic and mesoscale dynamical forcing